The Influence Of Family Environment, Self Efficacy and Tolerance For Risk on Students’ Entrepreneurial Interest - Oscarius Yudhi Ari Wijaya; Sarbaeni Sarbaeni (International Journal of Economics Development Research (IJEDR), 2023)
Growing intention in entrepreneurship among the young generation becomes one solution in dealing with intellectual unemployment which is increasing due to lack of awareness among the younger generation to create their own jobs. This study aims to analyze and examine the influence factors of family environment, self efficacy and tolerance for risk on entrepreneurial interest at Hamzanwadi University in East Lombok. The research used the quantitative with regression analysis method. The number of population amounted to 283 and the sampling method used was accidental sampling and applying the Slovin formula with an error rate of 5%. The number of samples used in this study amounted to 74 respondents source was distribution of questionnaires to college students, then the data were analyzed with IBM SPSS version 22. The data analysis was carried out by several tests such as validity test, reliability test, classic assumption, linear regression analysis and coefficient of determination test. The results of this study indicate that the partial, family environment, self-efficacy and tolerance for risk have a positive and significant effect on college students' entrepreneurship interest. Simultaneously, family environment, self-efficacy and tolerance for risk have a positive and significant effect on entrepreneurship interest of college students at Hamzanwadi University in East Lombok. The findings can be a reference for local government and universities to improve the quality of infrastructure that has a good impact on student entrepreneurial practices so as to increase interest in becoming an entrepreneur.